PENGARUH GAJI, DISIPLIN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWA CV. SRI KENCONO DESA KESAMBI RAMPAK KECAMATAN PANJI KABUPATEN SITUBONDO - Ika Wahyuni; Bagas Marta Wahyuda; Siti Soeliha (Relawan Jurnal Indonesia, 2020)
This study aims to determine the Effect of Salary, Work Discipline and Job Stress Against Employee Performance CV. Sri Kencono Kesambi Village Rampak, Panji District, Situbondo Regency. The method used is: multiple linear regression analysis, t test, F test, classic assumption test and coefficient of determination. The results of this study provide the following conclusions: the selected research object is in CV. Sri Kencono Kesambi Village Rampak, Panji district, Situbondo Regency. CV. Sri Kencono moves in the field of ready-to-eat food and beverage distributors PT. Mayora, various stimuli of work motivating factors can improve employee performance, in general, people working at a company have the goal of getting a salary to meet their daily needs. The results of Partial statistical test or t test shows the value for this salary variable is tcount -0,834> ttable -2,018, work stress variable X3 is tt 4.018> ttable 2.018 and this stressful work variable is tt 4.018> ttable 2.018 . Significant value of 0,000 <0.05. Simultaneous statistical test or F test shows the value of Fcount 87.408 ≥ F table 2.827 and a significant value of 0.000 <0.05. Based on the dominant test of the independent variable with the influence value of Salary variable X1 of -0.834 work discipline variable X2 of 0.269 and work stress variable X3 of 4.018. The coefficient of determination or R2 indicates a value of 0.346 from these results means that all variables are free of salary, work discipline and work stress have a contribution of 34.6% to the dependent variable of employee performance with a significant degree of determination, and the remaining 65.4% is influenced by other factors not included in the study.